Is Termination of Early Pregnancy Permissible for Controversial or Non-Medical Reasons? The Opinion of Final Year Students Faculty of Medicine University of Khartoum 2015. - Zaki, Asim Zaki Mohammed; Ahmed Ali, Alaa Abbas; Mohammed Ahmed, Lujain Mardi (Gezira Journal of Health Sciences, 2017)
pregnancy could be terminated therapeutically if its continuation will endanger mother's life. But there are many Situations in which early pregnancy is terminated for controversial or reasons which are strictly non medical examples:-Abortion on request (unplanned pregnancy, exposure to radiation, TORCH infection, teratogenic medicines, following rape, and existence of congenital abnormality), fetal selection, fetal reduction, some methods of birth control that interfere with implantation, and emergency contraception.